2010
DOI: 10.1086/649828
|View full text |Cite
|
Sign up to set email alerts
|

Large Changes in Fiscal Policy: Taxes versus Spending

Abstract: Executive SummaryWe examine the evidence on episodes of large stances in fiscal policy, in cases of both fiscal stimuli and fiscal adjustments in OECD countries from 1970 to 2007. Fiscal stimuli based on tax cuts are more likely to increase growth than those based on spending increases. As for fiscal adjustments, those based on spending cuts and no tax increases are more likely to reduce deficits and debt over GDP ratios than those based on tax increases. In addition, adjustments on the spending side rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
469
8
28

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 580 publications
(533 citation statements)
references
References 25 publications
28
469
8
28
Order By: Relevance
“…Contrary to recommendations by Alesina and Ardagna (2010) that spending cuts are more appropriate for stabilising the sovereign debt than tax increases, our results suggest the feasibility of revenue-based fiscal consolidation in Ukraine, as better tax collection as the main source of government revenue may contribute to economic growth even in the short run. At the same time, Ukraine would be better off if the government increased investments in infrastructure, health and education.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to recommendations by Alesina and Ardagna (2010) that spending cuts are more appropriate for stabilising the sovereign debt than tax increases, our results suggest the feasibility of revenue-based fiscal consolidation in Ukraine, as better tax collection as the main source of government revenue may contribute to economic growth even in the short run. At the same time, Ukraine would be better off if the government increased investments in infrastructure, health and education.…”
Section: Resultscontrasting
confidence: 99%
“…Although it is common in empirical studies to prefer government expenditure cuts over revenue-based consolidations (Alesina & Ardagna 2010, Alesina, Favero & Giavazzi 2015, including the experience of fiscal consolidations in the CEE countries for the 1991-2003 period (Afonso, Nickel & Rother 2006), there is evidence is that higher taxes could stimulate private consumption (Giavazzi et al 2005). Even though it is customary to consider tax multipliers for the CEE countries to be small and short--lived, as implied by contradictory results from VAR models with different identification techniques (Karagyozova-Markova, Deyanov & Iliev 2013), it is not confirmed that a positive revenue shock could be expansionary.…”
Section: Introductionmentioning
confidence: 99%
“…En effet, à plusieurs reprises le taux de croissance nominal des dépenses publiques dépasse celui du PIB (1998, 2001, 2002 et 2003), Alesina et Ardagna (2010) faisant d'ailleurs référence à une politique de relance budgétaire. Afin de saisir les sources de la croissance, nous calculons dans le tableau 5 les contributions de chaque composante de la demande à la croissance du PIB.…”
Section: Analyse Des Circonstances D'un Prétendu Succès Macroéconomiqueunclassified
“…Ce dernier cas s'est vu attribuer le doux sobriquet d'austérité expansionniste (cf. Giavazzi et Pagano, 1990;Alesina et Perotti, 1995;Alesina et Ardagna, 2010). Selon Perotti (2013), les explications en faveur de la consolidation budgétaire expansionniste peuvent être variées.…”
Section: Introductionunclassified
“…pueden ser expansivas (Alesina & Perotti, 1995;Alesina & Ardagna, 2010). En contraste, Guajardo, leigh & Pescatori (2014) argumentan que el método que usualmente se usa en esta literatura está sesgado para validar la hipótesis de austeridad expansiva; y muestran que la consolidación fiscal reduce la demanda privada y el nivel de producción.…”
unclassified